2018
DOI: 10.1155/2018/5845402
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Induces Apoptosis and Osteogenic Impairment through miR-22-Mediated Intracellular Oxidative Stress in Bone Marrow Mesenchymal Stem Cells

Abstract: Bone marrow mesenchymal stem cells (BMSCs) were characterized by their multilineage potential and were involved in both bony and soft tissue repair. Exposure of cells to ionizing radiation (IR) triggers numerous biological reactions, including reactive oxygen species (ROS), cellular apoptosis, and impaired differentiation capacity, while the mechanisms of IR-induced BMSC apoptosis and osteogenic impairment are still unclear. Through a recent study, we found that 6 Gy IR significantly increased the apoptotic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…One study found that radiation induced apoptosis of BMSCs through mir-22-exotrophic stress, which affected the repair and regeneration of bone tissue in irradiated sites [Liu et al, 2018].…”
Section: The Apoptosis Of Stem Cells Plays An Important Role In Variomentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that radiation induced apoptosis of BMSCs through mir-22-exotrophic stress, which affected the repair and regeneration of bone tissue in irradiated sites [Liu et al, 2018].…”
Section: The Apoptosis Of Stem Cells Plays An Important Role In Variomentioning
confidence: 99%
“…In the process of apoptosis, the cell elastic modulus and volume significantly decreased, and the cell surface roughness obviously increased; subsequently, the early apoptosis marker PS was detected, eventually the cells died. In combination with the previous molecular mechanism of stem cell apoptosis [Tower, 2015;Liu et al, 2018;Sun et al, 2018;Chen et al, 2015;Cui, 2007], stem cell apoptosis is not only a biological apoptotic signal cascade process, but is also accompanied by the reconstruction of mechanics and nanomorphology. These findings were helpful for further understanding and mastering the apoptosis of cells from the perspective of mechanics.…”
Section: Biology Open • Accepted Manuscriptmentioning
confidence: 99%
“…This may be explained due to the multifunction of this natural compound as follows: first, SAL may serve as a direct inhibitor on miR-22 formation, while the detailed mechanisms remain to be further explored. Second, miR-22 induces cellular senescence accompanied with oxidative stress and itself per se could mediate the intracellular oxidative stress [47][48][49], and SAL may directly prevent this process as it is a potent antioxidant according to our previous work and others' [21,39]. Third, SAL could rescue the declined SIRT1 by other pathways.…”
Section: Discussionmentioning
confidence: 76%
“…In the process of apoptosis, the cell elastic modulus and volume significantly decreased, and the cell surface roughness obviously increased; subsequently, the early apoptosis marker PS was detected, eventually the cells died. In combination with the previous molecular mechanism of stem cell apoptosis [Tower, 2015; Liu et al, 2018; Sun et al, 2018; Chen et al, 2015; Cui, 2007], stem cell apoptosis is not only a biological apoptotic signal cascade process, but is also accompanied by the modification of cell mechanics and nanomorphology. This study is helpful for further understanding and mastering the apoptosis of cells from the perspective of mechanics.…”
Section: Discussionmentioning
confidence: 99%
“…However, abnormal apoptosis of stem cells can lead to disease and/or poor self-repairing capability of the body. One study found that radiation induced apoptosis of BMSCs through mir-22-exotrophic stress, which affected the repair and regeneration of bone tissue in irradiated sites [Liu et al, 2018]. Moreover, the major metabolite 2,5-hexanedione of the organic solvent n-hexane, which is widely used in adhesive preparation, paints, varnishes, oil-based paint, and the food industry, can induce apoptosis of BMSCs via the mitochondria-mediated caspase-3 pathway [Sun et al, 2018; Chen et al, 2015] and nervous lesions [Cui et al, 2007].…”
Section: Introductionmentioning
confidence: 99%